Change of semen analysis parameters under the influence of psycho-emotional stress - Vorontsova, L. L.; Kovalenko, V. A.; Воронцова, Лоліта Леонідівна; Коваленко, Вікторія Анатоліївна (My University, 2025)
The article assesses spermogram of 904 clinically healthy men of reproductive age, who are living in the industrial city of Zaporizhzhіa (over a ten-year period). As a result of the study, only in 2022 – 2023 a number of pathological changes in spermograms (dyskinesis, teratozoospermia, decrease in the percentage of motile spermatozoa in the dynamic kinesisgram) were revealed, which is evidence of the deterioration of the fertility of the ejaculate and caused by the presence of additional psycho-emotional stress factors in these years. Thus, psychoemotional factors play a leading role in the development of reproductive disorders in men living in an industrial city, while the negative influence of environmental factors is secondary and manifests itself only with sufficiently powerful cumulative effects.
Keywords: spermogram; regional indicators; male infertility; fertility